Formation of oriented layered MoS2 from amorphous thin film revealed by polarized x-ray absorption spectroscopy - Krbal, Miloš; Přikryl, Jan; Prokop, Vít; Píš, Igor; Bondino, Federica; Kolobov, Alexander (My University, 2022)
MoS2 is a prototypical two-dimensional van der Waals (vdW) solid, where covalently bonded S–Mo–S triplets are held together by weaker vdW forces. In this work, we have studied structural transformation from a three-dimensional amorphous phase of MoS2 into a layered vdW crystal using S L2;3 edge x-ray absorption near-edge structure (XANES) spectroscopy with in-plane and out-of-plane polarized x-ray beam. The crystallization process, which starts from an isotropic amorphous phase, is accompanied by the establishment of vdW interaction between covalently bonded layers, resulting in the anisotropic nature of the crystalline phase. We have disclosed that the preferential growth of MoS2 layers along the (200) Bragg reflection commences immediately from the amorphous phase with no intermediate crystal orientations. We have additionally identified a unique signature in the S L2;3 edge spectrum that is associated with vdW bonds and can be possibly used to determine sulfur-based single-layered and multi-layered transition metal dichalcogenides.
Vznik orientovaného vrstveného MoS2 z amorfního tenkého filmu odhalený polarizovanou rentgenovou absorpční spektroskopií
Keywords: thin films; polarized X-ray absorption spectroscopy; MoS2; local structure; crystallization; van der Waals gap; tenké vrstvy; polarizovaná RTG absorpční spektroskopie; MoS2; lokální struktura; krystalizace; van der Waalsova mezera